(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Political marketing is a way that political organizations, politicians, political leaders, political parties, governments, and NGOs use marketing methods and concepts to create and develop their products and political understanding, Its purpose is to respond to marketing and involve communicating and interacting with the political market to achieve the desired effect. Political marketing is not just advertising management, but also political communication, election campaigning, and a strategy centered on political consumers that is, voters,who act as the drivers of market dynamics and how voters make decisions based on their needs over some time.Political Marketing Elements; (1) Political Product, (2) Push Marketing, (3) Pull Marketing, and (4) Polling. However, there are 3 marketing tools for political campaigns as follows: (1) The classification of marketing segments of the elector is Political Product, Marketing Promotion, and Political Place. (2) The positioning of candidates and parties is the application of political party policies, and the rebuilding of one’s image.And (3) Political Marketing Strategies were Sensation, Story, Speed, and Social Media.